Bismarckia nobilis: Bismarck Palm - Timothy K. Broschat (EDIS, 2015)
The Bismarck palm is a native of Madagascar that grows to a height of 30 to 60 feet with a spread of 12 to 16 feet. The massive 4-foot-wide costapalmate leaves are typically silver-green in color, but a light olive-green-leaved variety also exists. The persistent leaf bases are split, creating an attractive pattern on the 15–18-inch-diameter trunks. The dark brown male and female inflorescences are produced on separate trees, with females developing olive-brown fruit about 1.5 inches in diameter. The bold texture and color and eventual great height of this species make a strong statement in any setting, but can be overpowering in small residential landscapes. This revised 3-page fact sheet was written by Timothy Broschat, and published by the UF Department of Environmental Horticulture, February 2015. (Photo credit: T. K. Broschat)